Anatomical, Morphophysiological and Molecular Characterization of Brazilian Species of Cleomaceae - Parma, Daniele de Freitas (2021)
Cleomaceae is one of the 17 families of the order Brassicales, which comprises 26 genera and about 270 species. This cosmopolitan family has a great morphological and physiological diversity and due it is a sister group of Brassicaceae, to which the model plant Arabidopsis is inserted, it has been the subject of studies in several areas. However, despite being a promising family, there are few species characterized, so far only 15 have been physiologically characterized. Thus, this work aimed to characterize species of Cleomaceae occurring in Brazil. In this sense, visits to herbariums and collections were carried out in various regions in order to better understand the identity, ecology and distribution of each species. Thus, 22 species were sampled. Morphological and molecular characterization, based on five markers, showed that the Tarenaya series are monophyletic (Chapter 1) and that T. siliculifera is morphologically distinct from the species of the genus, so the recognition of a new monotype genus has been proposed (Chapter 2). In addition, we characterized the 22 species in terms of genome size, molecular phylogeny, anatomical, biochemical, and physiological characteristics (Chapter 3). In addition to determining the photosynthetic parameters, biochemical analyzes were performed on the leaves throughout the day (Chapter 4). Interestingly, the C 3 species groups exhibit clear variation in anatomical, physiological and biochemical parameters, suggesting a large natural variation among these species. Furthermore, unrecognized variation in leaf structure and physiology within the species studied indicates varying degrees of development of the C 3 -C 4 photosynthetic mechanism. Furthermore, the Brazilian Cleomaceae accessions characterized here exhibit a high genetic diversity and may represent different stages of development of the photosynthetic mechanism from C 3 to C 4 . Regarding the characterization of the sexual type of each flower (Chapter 5), the 20 morphospecies formed three four groups of sexual expression: andromonoicia, hermaphrodites, and polygamous. In addition, dichogamy and distyly were also observed, however, the species studied are self-compatible. Finally, a compilation of all available information about Cleomaceae is carried out in Chapter 6 in order to identify the characteristics of each group and indicate the advances in each area with the family. Keywords: Cleoserrata. Gynandropsis. Molecular phylogeny. Photosynthesis. Tarenaya.